Design and Validation of a Questionnaire to Measure Patient Experience in Relation to Hospital Nursing Care - Nieves López-Ibort; Angel Boned-Galán; Miguel Cañete-Lairla; Carmen Angustias Gómez-Baca; Marina Angusto-Satué; Josep-Oriol Cas; Ana Gascón-Catalán (MDPI AG, 2024)
The objective has been to develop and validate a questionnaire to know patient experience in relation to nursing care during their hospital stay in the Spanish healthcare setting. To know patient experience will improve the quality of care of the healthcare system; therefore, we must count on validated tools so it can be evaluated in an accurate way. Method: a questionnaire containing 29 items alongside socio-demographic questions was developed. It was distributed to 158 patients admitted to a tertiary hospital. The psychometric properties were assessed through principal components analysis and confirmatory factor analysis to evaluate construct validity, employing Cronbach's alpha to test reliability. Results: The final tool contains 17 items grouped into 5 dimensions: interrelations, nursing care, information during hospital stay, information about patient's rights, and discharge information. Two additional questions related to pain were added. The questionnaire showed adequate validity and reliability. Conclusions: we describe a new tool validated and adapted to the Spanish healthcare setting with adequate validity and reliability to assess patient experience with nursing professionals during hospital stay. This tool will serve to identify areas for improvement in hospital nursing care and as an instrument in the management and supervision of nursing teams.